Union of the Comoros : 2005 Article IV Consultation and First Review Under the Staff-Monitored Program; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Union of the Comoros. (IMF Staff Country Reports; Country Report ;, 2005)
This paper analyzes the 2005 Article IV Consultation and First Review Under the Staff-Monitored Program (SMP) for the Union of the Comoros. Economic growth remained lackluster in 2004 owing to a depressed world demand for vanilla and crop, and cattle diseases. Government revenue stagnated, while wage outlays rose significantly on account of hirings associated with the new constitutional arrangements. Monetary policy remained prudent, but inflation increased slightly. Performance under the SMP in the first quarter of 2005 was mixed.